2008
DOI: 10.1055/s-2008-1058817
|View full text |Cite
|
Sign up to set email alerts
|

Endoskopische transthorakale Sympathektomie bei paraneoplastischem Raynaud-Syndrom

Abstract: Six months after nephrectomy for renal-cell carcinoma and during treatment with interferon-alpha and vinblastin, a 70-year-old patient developed necrotizing Raynaud's phenomenon in both hands (at first: pain, livid skin and hyperhidrosis; later: painful acral ulcers; finally: trophic changes plus almost complete impairment of mobility and fine movements in both hands). These changes persisted even after the end of chemotherapy and despite several months on aspirin, naftidrofuryl, nitrates and glucocorticoids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Various prior case-reports have demonstrated that treatment of the malignancy also causes improvement with regards to the paraneoplastic Raynaud’s phenomenon 6 15 24…”
Section: Discussionmentioning
confidence: 99%
“…Various prior case-reports have demonstrated that treatment of the malignancy also causes improvement with regards to the paraneoplastic Raynaud’s phenomenon 6 15 24…”
Section: Discussionmentioning
confidence: 99%
“…One sign of the paraneoplastic syndrome is digital ischaemia. In one such reported case with severe bilateral Raynaud's phenomenon, bilateral sympathectomy permanently relieved ischaemia of the hands until demise of the patients after 10 months [192].…”
Section: Vasoconstrictive Ischaemiamentioning
confidence: 99%
“…Zur symptomatischen Therapie werden neben der Analgesie mit Opiaten Nitrosalbe, Kalziumantagonisten (prä-ferenziell Nifedipin), Acetylsalicylsäu-re, Heparin und die pharmakologische und/oder interventionelle SympathektoAbb. 2 [7] als auch eine CT-gesteuerte Neurolyse unterhalbTh 3 [2] als erfolgreich beschrieben worden. Letztlich sind die verschiedenen Behandlungsansätze, abgesehen von der Therapie des Malignoms, was zur kompletten Remission der Paraneoplasie füh-ren kann [11], meist lediglich palliativ und nur vorübergehend wirksam: Das Auftreten eines paraneoplastischen RaynaudPhänomens ist oftmals ein "signum mali omnis".…”
Section: Therapiemöglichkeitenunclassified
“…Im Blutbild fanden sich eine normochrome, normozytäre Anämie von 10,5 g/dl (12,[3][4][5][6][7][8][9][10][11][12][13][14][15]8) und eine leichte Leukozytose von 11,5 G/l (3,7-9,6). Der direkte Coombs-Test, Kälteagglutinine, Kryoglobuline, Rheumafaktoren, ANA, ANCA, Komplement C3 und C4, HIV, Hepatitis B-und C-Serologien sowie Blutkulturen waren negativ bzw.…”
unclassified